Preparation and Evaluation of Hydrogel Containing Prednisolone Nanoparticles - Walaa A. Saihood; Hayder K. Abbas (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2023)
Currently, nanoparticles technology is well known and it used to augment the rate of drug dissolution and considerably increased bioavailability. Nanoparticles have been combined with hydrogel to form nanoparticle-hydrogel hybrid system as a substitute to conventional dosage forms.